DEVELOPING WRITING MATERIALS FOR THE FIRST GRADE STUDENTS AT SMA NEGERI 1 BINJAI - Feby Maulida Nasution and Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2018)
The objectives of this study are to investigate the relevant English writing materials for the first grade students at SMA Negeri 1 Binjai and to develop the relevant English writing materials through contextualization for the first grade students at SMA Negeri 1 Binjai. This research was conducted based on educational research and development (R&D) through three steps: 1) evaluation and need analysis, 2) course design, and 3) materials validation. The subjects of this study were the first grade students at SMA Negeri 1 Binjai and the English teacher at SMA Negeri 1 Binjai. The instruments in this study were questionnaire and the question sheet. Questionnaire was administered to the students, meanwhile the question sheet was used while interviewing the English teacher. The data which were gathered from the evaluation and need analysis were analyzed in the descriptive analysis, and the result of the expert judgment about the quality of the developed materials used quantitative descriptive analysis. The result of this study was a coursebook of writing materials based on contextualization. The contextualized materials consisted of three chapters which were related to the students’ real experience. The first chapter was my lovely people, the second chapter was my amazing city and the third chapter was the memorable moments in my life. Based on the experts’ judgment result, the score of the developed materials was 90 which belong to excellent category, since the range was (80-100).